2012
DOI: 10.1080/15287394.2012.697839
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation of Biological Activities in Venoms from Wild and CaptiveBothrops jararaca

Abstract: The venom of Bothrops jararaca is composed of complex mixture of molecules, mainly lectins, metalloproteinases, serinoproteinases, desintegrins, phospholipases, and peptides. This composition may vary according to the snake's age, gender, and region of origin. The aim of the was to determine individual variation in Bothrops jararaca venom in the Botucatu region, Sao Paulo State, Brazil, by means of enzymatic, biochemical, and pharmacological characterization, utilizing in vitro tests and biological assays. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Differences in the composition and activity of snake venoms from the same species are a worldwide researchers concern. These differences can influence directly in the antivenom production and in the success of patient treatment [54][55][56][57].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the composition and activity of snake venoms from the same species are a worldwide researchers concern. These differences can influence directly in the antivenom production and in the success of patient treatment [54][55][56][57].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst extensively studied, intraspecific variability still needs more elucidation, as it could have an impact in snakebite treatment [ 36 , 61 ]. In this work, we analyzed the venom of captive-born Brazilian lancehead at different life stages in controlled environment.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we reported that pools of venoms from snakes collected from the floodplain habitat differed from the others on functional activities [50,51] and higher individual venom variability was observed among this group, suggesting that a higher variability may be a characteristic favored in snakes inhabiting this type of environment. The major venom-enzymatic activities varied in the nine specimens included in this group and these changes found no correlation to the predicted composition of the fractions whose peaks showed differences in height, suggesting that small fluctuations in the expression of different isoforms of these compounds, recorded due to the high sensitivity of the enzymatic assays, may contribute to this apparent functional variability of the venoms, as reported in other comparative studies using enzyme assays [40,44,52]. Nevertheless, it is important to note that the variability within this group of nine snakes was related to toxins present at low abundance in the venoms.…”
Section: Discussionmentioning
confidence: 68%
“…This hypothesis has been tested recently by different groups and the results are still inconclusive. Some evidence indicates little influence of captivity maintenance on venom composition [26,40,41,42,43], while others show evidence that the environmental changes due to introduction to captivity may modify venom composition [44]. However, these studies compare venoms from groups of snakes recently caught in the wild with groups of other specimens maintained for a long term under captivity.…”
Section: Introductionmentioning
confidence: 99%